2022
DOI: 10.3390/app122312333
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Truck Tractor Tire Damage in the Context of the Study of Road Accident Causes

Abstract: There are many accidents in road traffic involving both heavy goods vehicles and passenger vehicles, and the interpretation of the causes of some accidents can be very difficult. The paper presents the results of an analysis of the road accident causes involving a truck and two passenger cars. The hypothesis was verified that the incident took place after the damage to the front wheel of the truck, which resulted in an uncontrolled change of the direction of its travel and leaving the lane in the opposite dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…Where 𝜎 𝑑𝑒𝑣 = 𝜎 𝑣𝑜𝑙 − 𝜎 and 𝜎 𝑣𝑜𝑙 = In line with the tire's known failure zone in the static experimental tests [9], [10], we observed a densification of stresses in the sidewall region at the right of the contact zone caused by the lateral deformation associated with the radial deformation.…”
Section: Von Mises Stress In Mpasupporting
confidence: 79%
See 1 more Smart Citation
“…Where 𝜎 𝑑𝑒𝑣 = 𝜎 𝑣𝑜𝑙 − 𝜎 and 𝜎 𝑣𝑜𝑙 = In line with the tire's known failure zone in the static experimental tests [9], [10], we observed a densification of stresses in the sidewall region at the right of the contact zone caused by the lateral deformation associated with the radial deformation.…”
Section: Von Mises Stress In Mpasupporting
confidence: 79%
“…Wang et al [8] instead adopted a linear elastic composite model and validated its performance with experimental tests. The main drawback associated with the laminar approach is that it is difficult to model and predict the failure mechanism [9], [10] of the matrix, the rebar, or the cohesive bond connecting them. Therefore, detailed modeling with real rebars not only allows us to get the previously known results but also opens the doors to failure modeling.…”
Section: Introductionmentioning
confidence: 99%
“…PM in the air of predominantly densely built-up cities is a serious issue and causes premature deaths 9,10 . There is also a danger of suspension destruction in connection with a sudden body descent that can be a reason for a car accident, as also given in publication 11 in which the authors concluded that the axle road is the main cause of heavy weight vehicles' malfunctions on highways in Poland, and then there is an increased risk of congestions due to obstructions, which is a frequent phenomena on the highways. Thus, the axle load has a negative impact on the economics, air quality as well as supply chains [12][13][14] .…”
Section: Consequences Of Load Distribution In Selected Vehicles In Th...mentioning
confidence: 92%
“…The tire consists of a tire casing and a rim. An automobile radial tire casing with classical construction [ 3 ] consists of rubber with textile and steel cords [ 4 ] in a tire crown and carcass, Figure 1 . The construction parts applied to the radial tire casings of the passenger car are a steel cord belt, a textile carcass, and a textile overlap belt [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%